Fixed-Time Leader-Follower Output Feedback Consensus for Second-Order Multiagent Systems - Tian, Bailing; Lu, Hanchen; Zuo, Zongyu; Yang, Wen (IEEE transactions on cybernetics, 2019)
This paper addresses the fixed-time leader-follower consensus problem for second-order multiagent systems without velocity measurement. A new continuous fixed-time distributed observer-based consensus protocol is developed to achieve consensus in a bounded finite time fully independent of initial condition. A rigorous stability proof of the multiagent systems by output feedback control is presented based on the bi-limit homogeneity and the Lyapunov technique. Finally, the efficiency of the proposed methodology is illustrated by numerical simulation.